The Impact of Behavioral Couple Therapy on Attachment in Distressed Couples. (25th April 2013) - Benson, Lisa A.; Sevier, Mia; Christensen, Andrew
Abstract : Emotion‐focused therapy (EFT; Greenberg & Johnson, 1988 Emotionally focused therapy for couples . New York: Guilford Press) is anchored in attachment theory (Johnson, 2003 Attachment processes in couples and families . New York: Guilford) and considers change in attachment schemas essential in the process of improving satisfaction in relationships (Johnson, 1999, Research and couples therapy: Where do we go from here? American Family Therapy Academy Newsletter ). However, there are little data on how measures of attachment change over the course of EFT or any other couple therapy. The current study examines whether increases in attachment security predict improvements in marital satisfaction during behavioral couple therapy, which would suggest that change in attachment style is a key process variable even for a non‐attachment‐focused treatment. Multilevel models of data from 134 couples participating in a randomized clinical trial of integrative behavioral couple therapy and traditional behavioral couple therapy (Christensen et al. Journal of Consulting and Clinical Psychology, 72, 2004, 176) indicate that although there is a trend for early change in attachment‐related anxiety and avoidance to predict later change in marital satisfaction, early change in marital satisfaction strongly predicts change in attachment‐related anxiety through the end of treatment and 2‐year follow‐up. These findings suggest that changes in satisfaction may lead to changes in attachment rather than the reverse and that change in attachment may not be the mechanism of change in all efficacious couple therapy.